Kinetics of Immune Cell Mobilization during Acute Aerobic Exercise in Healthy Adults - Adammek, Frederike; Wences Chirino, Tiffany Y.; Walzik, David; Trebing, Sina; Belen, Sergen; Renpening, Daniel; Zimmer, Philipp; Joisten, Niklas (International Journal of Sports Medicine, 2024)
While pre-post differences in immune cell mobilization after acute aerobic exercise are well investigated, less is known about when and to what extent immune cells are mobilized during acute aerobic exercise. This experimental trial aimed to investigate the detailed kinetics of circulating immune cells in twelve healthy adults (n=6 females) who completed a 40-min aerobic exercise bout at 60% of the participantsʼ V̇O2peak on a bicycle ergometer. Cellular inflammation markers and sex-dependent differences in circulating immune cells were analyzed. Blood samples were taken immediately before, after warm-up, during exercise after 5 min, 10 min, 15 min, 30 min, 40 min (cessation), and 60 min post exercise. Significant increases in leukocytes (p<0.001), lymphocytes (p<0.001), neutrophils (p=0.003) and platelets (p=0.047) can be observed after 5 min of exercise. The cellular inflammation markers show significant alterations only post exercise. Significant sex differences were observed for neutrophils (p=0.049) and neutrophil-to-lymphocyte ratio (p=0.007) one hour post exercise. These results indicate that i) leukocytes are already mobilized after 5 min of moderate-to-vigorous aerobic exercise, ii) the magnitude of exercise induced leukocyte mobilization is dependent on exercise duration, iii) integrative cellular inflammation markers are only altered after exercise cessation, and iv) the observed effects might be sex-dependent.
Keywords: circulating immune cells; aerobic exercise; NLR; endurance exercise; exercise immunology